Konsep Integrasi Pendidikan Islam dan Literasi Sains sebagai Jawaban Krisis Nilai Abad 21 - Handayani, Satri (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This study aims to explore the integration of Islamic education and scientific literacy as a conceptual solution to the 21st-century values crisis. The research adopts a library research method with a descriptive-conceptual approach, analyzing recent academic literature related to Islamic education, scientific literacy, and contemporary moral issues. The findings reveal that this integration is not merely the combination of two disciplines, but an epistemological alignment between revelation and scientific rationality, reflecting the harmony of faith and knowledge. Islamic education plays a vital role in shaping students’ character through spiritual and ethical values, while scientific literacy fosters critical thinking and environmental awareness. Effective learning strategies involve scientific, holistic, and transdisciplinary approaches that balance affective and cognitive development. The study concludes that the integration of Islamic values and scientific principles can foster a more comprehensive, adaptive, and meaningful educational paradigm, capable of producing intellectually excellent individuals with strong moral character and deep social and spiritual awareness.